An Energy Investigation of An Organic Rankine Cycle Utilizing Three Organic Fluids - Rabah Touaibi; Ozlem Boydak; Hasan Koten (Hittite Journal of Science and Engineering, 2020)
This study presents an energy study of an Organic Rankine Cycle ORC by comparing three organic fluids. The latter is considered as a promising cycle for the conversion of heat into mechanical energy adapted to low-temperature heat sources; it uses more volatile organic fluids than water, which generally has high molecular weights, thus allowing operating pressures at temperatures lower than those of the traditional Rankine cycle. This study devoted to the energy analysis of the ORC cycle, taking into account the effect of the operating temperatures and the choice of the organic fluid on the cycle performance. The utilized three fluids were Toluene, R245fa and R123. The results obtained show that the Toluene organic fluid has the best energy efficiency of the cycle with 7.45%.